Accountability of the International Monetary Fund - Carin, Barry, 1946- (Voices in development management., 2005)
Brings together leading experts from all over the world to further the debate on the various dimesions of accountability of IMF to its various sharholders and stakeholders. Having fully explored how the notion of accountability can be pragmatically applied it then tests various alternative appriaches and makes some recommendations.